Organization and Management of Intensive Care Unit, correlation of team climate with job satisfaction of the nurses in the ICU - Diamantopoulou, Christina; Platis, Charalampos; Lahana, Eleni; Stergiannis, Pantelis; Intas, George (Health & Research Journal, 2022)
Introduction: The correlation between team climate and job satisfaction has been studied by researchers worldwide, but only a handful of them have dealt with the reality of Intensive Care Units (ICU). Team climate can contribute to nurses’ job satisfaction, thus increasing their efficiency and effectiveness. Especially during a pandemic, such as Covid-19, the investigation of team climate and job satisfaction is of great importance. Purpose: The purpose of this study was to investigate the correlation between team climate and job satisfaction of nurses in ICU and among the fear of Covid-19. Methodology: This is a contemporary study. The sample of the study is consisted of nurses and nurses’ assistants of a Greek public hospital ICU and special units. The Anderson & West Team Climate Inventory (TCI), the Paul E. Spector Job Satisfaction and the Fear of COVID-19 Scale were used for data collection. The statistical analysis of the data was done with the statistical program SPSS for Windows (version 21). Results: Out of the 212 nurses, 170 responded to the questionnaire (response rate 80.2%). The team climate was generally described as moderate. Especially, the dimensions of communication-innovation, team goals and the way they work assessed as moderate. Job satisfaction was described as moderate. Relationships with the manager, the nature of the work and communication, characteristics of job satisfaction, were evaluated with a high score, while payment, benefits and promotion were evaluated with low score. The fear of Covid-19 scale had low score, indicating that the feeling of fear was at low levels. Conclusions: The team climate and job satisfaction of ICUs nurses of the hospital was characterized as moderate, while the fear levels due to Covid-19 were low. Furthermore, the team climate was positively correlated with job satisfaction. In contrast, neither team climate nor job satisfaction were associated with fear of Covid-19.